How many species of whipworms do we share? Whipworms from man and other primates form two phylogenetic lineages - Doležalová, Jana; Oborník, Miroslav; Hajdušková, Eva; Jirků, Milan; Petrželková, Klára J.; Bolechová, Petra; Cutillas, Cristina; Callejón, Rocio; Jaroš, Jozef; Beránková, Zuzana; Modrý, David (Akademie věd ČR, 2015)
The whipworms, i.e. parasitic nematodes of the genus Trichuris Roederer, 1761, infect a variety of mammals. Apparently low diversity of primate-infecting species of Trichuris strongly contrasts with the high number of species described in other mammalian hosts. The present study addresses the diversity of whipworms in captive and free-ranging primates and humans by analysing nuclear (18S rRNA, ITS2) and mitochondrial (cox1) DNA. Phylogenetic analyses revealed that primate whipworms form two independent lineages: (i) the Trichuris trichiura (Linnaeus, 1771) clade comprised of genetically almost identical whipworms from human and other primates, which suggests the ability of T. trichiura to infect a broader range of primates; (ii) a clade containing primarily Trichuris suis Schrank, 1788, where isolates from human and various primates formed a sister group to isolates from pigs; the former isolates thus may represent of more species of Trichuris in primates including humans. The analysis of cox1 has shown the polyphyly of the genera Trichuris and Capillaria, Zeder, 1800. High sequence similarity of the T. trichiura isolates from humans and other primates suggests their zoonotic potential, although the extent of transmission between human and other non‐human primates remains questionable and requires further study.
Keywords: Trichuris; phylogeny; diversity; zoonotic potential; humans